The Implementation of Problem Based Learning Model: An Effort in Upgrading Students' Problem-Solving Skills (Jurnal Pendidikan Fisika, 2022)
Problem-based learning (PBL) is one of the various effective learning models used by a teacher in teaching physics. In the PBL model, students are encouraged to ask and answer questions to improve their problem-solving skills. This study aims to analyze whether the PBL model with the hybrid method can improve students' problem-solving abilities in learning physics. This research is pre-experimental research. The research sample is class X MIPA 1 at SMAN 17 Surabaya, taken by using the purposive sampling technique. The research was conducted in a hybrid learning (offline and online) using a one-group pretest-posttest design. Data were collected through observation and tests in the form of pre-test and post-test. The data were then analyzed using quantitative descriptive methods. The results showed that the n-gain value obtained was 0.31 (medium category). The paired t-test results obtained have a sig value. (2-tails) of 0.000, which is smaller than sig. 0.05. Based on these results, it can be concluded that learning physics with the PBL model is quite effective in improving students' problem-solving abilities.